Inherited cancer case studies - Hodgson, Shirley (Henry Stewart Talks, 2021)
Non-paternity, Clinical observation, Pedigree information, Non-paternity, Indirect genetic testing, Genetic variants, Panel testing, Modifiers of penetrance, Tests in identical twins